Philosophy : the classic readings - Cooper, David E. [ (David Edward)] , 1942-; Fosl, Peter S. (Wiley-Blackwell, 2010)
A collection of works of philosophy from ancient to modern times. It draws on both Eastern and Western philosophical traditions. It features original readings from more than a hundred of the world's great philosophers - from Lao Tzu, Confucius, the Buddha, Plato, amkara, Aquinas, al-Ghaz li, Kant, and Kierkegaard, to Wittgenstein, and Heidegger.